Students’ Engagement in Personal Writing - Eldytacia, Valecia Najwa; Wijayatiningsih, Testiana Deni; Budiastuti, Riana Eka (UM Purwokerto Press, 2025)
There has been a rise in the number of mental health problems that college students are suffering as a direct result of the increased levels of stress that are present in the university environment. Students can effectively communicate their emotions through writing activities such as maintaining a diary, writing poetry, or engaging in introspective writing. On the other hand, educational institutions in Indonesia continue to overlook research questions about how students can improve their mental health through the use of personal writing. The purpose of this study is to investigate how children utilize writing as a means of effectively expressing their feelings and preserving their mental health. Researchers from Universitas Muhammadiyah Semarang recruited thirty students from the second, sixth, and eighth semesters to participate in the study. A quantitative and descriptive method was utilized in the investigation. To collect the information, we conducted a survey consisting of a single question. After engaging in activities that involved personal writing, the majority of participants in the survey reported feeling more emotionally balanced and experiencing lower levels of stress. The study's findings revealed this. The act of writing helped them become more self-aware, which in turn enhanced their emotional intelligence and problem-solving abilities. The results of the study suggest that students may be able to improve their mental health via the use of personal writing rather than through the use of pharmaceutical therapies. Instruction in reflective writing should be provided to students at educational institutions to promote the mental health of children.